Perbandingan Penagangan Hukum Anak Penggunaan Narkoba Di Indonesia Dan Malaysia - Dimas Bayunegara; Alamsyah; Mario Marco (Catalist Indo Publisher, 2025)
The increasing rate of drug abuse among children and adolescents has become a serious concern that demands urgent attention from all levels of society. The severity of this issue calls for a united effort to combat drug trafficking and promote stronger legal frameworks that address the specific needs of young drug users. In particular, law enforcement approaches toward children and adolescents involved in drug abuse should emphasize not only criminal penalties but also rehabilitation and child protection. This study aims to compare how Indonesia and Malaysia legally handle cases involving juvenile drug offenders. Employing the Systematic Literature Review (SLR) method, this research analyzes various national legal documents, policies, and academic perspectives to explore the similarities and differences in both countries’ legal treatments. In Indonesia, the legal response to children involved in drug abuse is guided by a restorative justice approach, which is embedded in the Narcotics Law and the Juvenile Criminal Justice System Law. These laws focus on rehabilitation and reintegration into society, rather than solely on punitive measures. Meanwhile, Malaysia also adopts a comparable framework through several pieces of legislation, including the Dangerous Drugs Act 1952, the Child Act 2001, and the Juvenile Courts Act 1947. These laws aim to strike a balance between punishment and protection, acknowledging the unique status of children in conflict with the law. In conclusion, while both countries adopt progressive strategies to deal with juvenile drug abuse, the implementation reflects each nation’s distinct legal system and socio-cultural context.